Journeys of the Mind A Life in History - Brown, Peter; Brown, Peter (Princeton University Press, 2023)
A beautifully written personal account of the discovery of late antiquity by one of the world$1 (Bs most influential and distinguished historiansThe end of the ancient world was long regarded by historians as a time of decadence, decline, and fall. In his career-long engagement with this era, the widely acclaimed and pathbreaking historian Peter Brown has shown, however, that the (3z(Bneglected half-millennium(3y (Bnow known as late antiquity was in fact crucial to the development of modern Europe and the Middle East. In Journeys of the Mind, Brown recounts his life and work, describing his efforts to recapture the spirit of an age. As he and other scholars opened up the history of the classical world in its last centuries to the wider world of Eurasia and northern Africa, they discovered previously overlooked areas of religious and cultural creativity as well as foundational institution-building. A respect for diversity and outreach to the non-European world, relatively recent concerns in other fields, have been a matter of course for decades among the leading scholars of late antiquity.Documenting both his own intellectual development and the emergence of a new and influential field of study, Brown describes his childhood and education in Ireland, his university and academic training in England, and his extensive travels, particularly in the eastern Mediterranean and the Middle East. He discusses fruitful interactions with the work of scholars and colleagues that include the British anthropologist Mary Douglas and the French theorist Michel Foucault, and offers fascinating snapshots of such far-flung places as colonial Sudan, midcentury Oxford, and prerevolutionary Iran. With Journeys of the Mind, Brown offers an essential account of the (3z(Bgrand endeavor(3y (Bto reimagine a decisive historical moment.s